1957
DOI: 10.1107/s0365110x57001449
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic configuration of the aspartate ion in the crystal structure of zinc, cobaltous and nickelous aspartate trihydrate

Abstract: The salts of L-aspartic acid with divalent zinc, cobalt and nickel crystallize as tri-hydrates, and are isomorphous. Unit-cell dimensions are:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The preliminary coordinates of the main atoms are given in Table 33. More precise data have been obtained from the isomorphous salts ot L-aspartic acid with Zn z +, Co z +, and Niz+ [72], which crystallize as trihydrates with space group P2 1 2 1 2 1 and the following cell parameters: Doyne and Pepinsky deduced the absolute configuration for the cobalt salt on the basis of anomalous x-ray scattering. The resulting coordinates were assigned to the zinc salt and then were refined by least squares from the three-dimensional set of intensities.…”
Section: Monoaminodicarboxylic Acidsmentioning
confidence: 99%
“…The preliminary coordinates of the main atoms are given in Table 33. More precise data have been obtained from the isomorphous salts ot L-aspartic acid with Zn z +, Co z +, and Niz+ [72], which crystallize as trihydrates with space group P2 1 2 1 2 1 and the following cell parameters: Doyne and Pepinsky deduced the absolute configuration for the cobalt salt on the basis of anomalous x-ray scattering. The resulting coordinates were assigned to the zinc salt and then were refined by least squares from the three-dimensional set of intensities.…”
Section: Monoaminodicarboxylic Acidsmentioning
confidence: 99%
“…The zinc, nickel, and cobalt salts were first reported by Doyne et al (1957), who only gave the unit cell dimensions. As later works established the structure for the zinc (Kryger and Ramsussen 1973;Zhang et al 2004) and the manganese analog Sekizaki (1979) 3.8 Asparagine, Glutamine, Aspartic Acid, and Glutamic Acid (Schmidbaur et al 1988), the agreement of the unit cell dimensions allows the conclusion that all four salts crystallize in the same structure.…”
Section: Tris(l-cysteinato-s)-bismuth Monohydrate Comprises [3]-coordmentioning
confidence: 98%
“…However, the bond lengths and angles within the cobaltate anion in (I) are in good agreement with those found in other structures containing this type of anion such as, for example, those described by Oonish et al (1973Oonish et al ( , 1975 and several other related structures. In contrast, recourse to the Cambridge Structural Database (Version 5.26; Allen, 2002) by means of the Chemical Database Service of the EPSRC (Fletcher et al, 1996) has revealed only one example of a cobaltous aspartate species, namely cobaltous aspartate trihydrate, (II) (Doyne et al, 1957), which is polymeric, has a Co:asp ratio of 1:1 [as distinct from 1:2 in (I)] and displays different (slightly longer) Co-N and C-O bond distances from those observed in the cobaltate anion in (I). It seems reasonable to suggest that, had not oxidation of the Co II of the starting material to Co III taken place resulting in the formation of (I), then (II) might well have been the product of the reaction.…”
Section: Figurementioning
confidence: 99%